Efforts to Reduce Plastic Waste Through Making Environmentally Friendly Shopping Green Bags at the Berkah Balai Baru Waste Bank - Novia Wirna Putri; Septia Pristi Rahmah; Dhea Lulu Fichriyah; Elvira Radhiatul Febriani; Areta Ardiningrum; Ahmad Adhitya Risyanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The Berkah Balai Baru Waste Bank was established on 20 November 2021. The waste management activity running at this Waste Bank is the waste deposit activity. Another program that has yet to be implemented is empowering waste bank officers and customers to make green bags to reduce plastic waste. Waste bank officers still need to gain the skills to create green bags. This service activity aims to increase people's insight into the dangers of plastic waste for environmental health and improve people's skills in making green bags. The educational methods used are persuasive communication, lectures, and two-way dialogue. During training, the method used is the product creation and practice training method; during activity mentoring, monitoring and evaluation of activities were carried out. This community service activity targets officers and customers of the Berkah Balai Baru waste bank. The results of the community service activities were that after carrying out the pre and post-test and comparing the score results, it was found that there was an increase in participants' knowledge by 29.9%, and there was participant enthusiasm, as shown by the feedback during the discussion session. Waste bank officers have been able to make shopping bags that can be used when shopping and can be a business opportunity for the Berkah Balai Baru Waste Bank. With this activity, waste bank officers have contributed to reducing plastic waste in the environment.